Resveratrol Ameliorates Glucocorticoid-Induced Bone Damage in a Zebrafish Model - Luo, Qun; Liu, Shengbo; Xie, Liming; Yu, Yongjie; Zhou, Limin; Feng, Yuzhen; Cai, De (Frontiers in Pharmacology, 2019)
Resveratrol (Res) is a multi-functional polyphenol compound that has protective functions in the cardiovascular and neurodegenerative diseases. This study was designed to evaluate the effect of Res on dexamethasone-induced osteogenic differentiation and bone mineralization in zebrafish (Danio rerio). Our results showed that dexamethasone sodium phosphate (Dex) exposure decrease the green fluorescence areas and the integrated optic density (IOD) values in the head bones of zebrafish larvae of the TG strain (SP7: EGFP) in a dose-dependent manner and could decrease the alizarin red-stained areas in the skeleton and spinal bones of zebrafish larvae of the AB strain in a dose-dependent manner. Dex (15 μmol/L) exposure significantly decreased the bone mineralization areas and the IOD values in the head bones of zebrafish larvae (P< 0.01), and Res (150 μmol/L) could significantly increase the green fluorescence levels and bone mineralization levels in the head bones of zebrafish treated with Dex. Taken together, our data suggest that Res could effectively improve the bone mineralization of bone damage by glucocorticoid-induced in a zebrafish model and that Res is a potential drug for the prevention of osteoporosis.